ANALYSIS THE USE OF INSTRUCTIONAL MEDIA ON TEACHING ENGLISH TO YOUNG LEARNER AT ELEMENTARY SCHOOL IN BANDUNG - Resti, Resti; Rachmijati, Cynantia (IKIP Siliwangi, 2020)
Instructional media is a tool used by teachers to explain material in the classroom, which is anything that can be used to stimulate children's thoughts, attention, and feelings, to encourage the learning process. Therefore the teacher of English for young learner must create a fun classroom setting by using media, beside of technique and method to attract students attention. The aimed of this study is to describe the teacher's preparation and explain the use of media in the classroom. This study uses descriptive qualitative methods, by collecting data using interviews, observation, and document analysis. The results of this study indicate that in preparing the media, the teacher must understand the material to be taught and adjust the media to be used with the material. The use of media depend on the material, and on this research the media used by teachers are coursebooks, video, realia and picture. Such as video to train on students' speaking and listening skills. Picture is to increase children's knowledge about vocabulary. Coursebooks are used to practice student's reading and writing skill, while realia is used to introduce children to real subject. Keywords: English, Young learner, Instructional Media